2019
DOI: 10.1002/ehf2.12482
|View full text |Cite
|
Sign up to set email alerts
|

Sex disparities in acute kidney injury complicating acute myocardial infarction with cardiogenic shock

Abstract: Aims To evaluate sex‐specific disparities in acute kidney injury (AKI) complicating acute myocardial infarction‐related cardiogenic shock (AMI‐CS) in the United States. Methods and results This was a retrospective cohort study from 2000 to 2014 from the National Inpatient Sample (20% sample of all hospitals in the United States). Patients >18 years admitted with a primary diagnosis of AMI and concomitant CS that developed AKI were included. The endpoints of interest were the prevalence, trends, and outcomes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 18 publications
(31 reference statements)
4
45
0
1
Order By: Relevance
“…This is similar to prior studies of ECMO and Impella which found higher risk of bleeding requiring blood transfusion and development of acute kidney injury (AKI) [8]. This is potentially related to increased risk of hemolysis, vascular complications and hypovolemia causing pre-renal hypoperfusion [8]. In our study there were no unique predictors of complications in pLVAD, however, risk of complication in IABP was associated with advanced age, non-ST-segment elevation Multivariable adjusted odds ratios (95% confidence intervals) � for occurrence of complications (A) and in-hospital mortality in admissions with complications in AMI-CS supported by pLVAD compared to IABP; all p<0.001 where 95% confidence interval does not include unity.…”
Section: Plos Onesupporting
confidence: 90%
See 2 more Smart Citations
“…This is similar to prior studies of ECMO and Impella which found higher risk of bleeding requiring blood transfusion and development of acute kidney injury (AKI) [8]. This is potentially related to increased risk of hemolysis, vascular complications and hypovolemia causing pre-renal hypoperfusion [8]. In our study there were no unique predictors of complications in pLVAD, however, risk of complication in IABP was associated with advanced age, non-ST-segment elevation Multivariable adjusted odds ratios (95% confidence intervals) � for occurrence of complications (A) and in-hospital mortality in admissions with complications in AMI-CS supported by pLVAD compared to IABP; all p<0.001 where 95% confidence interval does not include unity.…”
Section: Plos Onesupporting
confidence: 90%
“…Hepatic failure and ECMO support were strong predictors of worse outcomes. This is similar to prior studies of ECMO and Impella which found higher risk of bleeding requiring blood transfusion and development of acute kidney injury (AKI) [8]. This is potentially related to increased risk of hemolysis, vascular complications and hypovolemia causing pre-renal hypoperfusion [8].…”
Section: Plos Onesupporting
confidence: 88%
See 1 more Smart Citation
“…During the period between 1 January 2000 through 31 December 2016, a retrospective cohort of admissions from the HCUP-NIS with a primary diagnosis of AMI (International Classification of Disease-9 Clinical Modification [ICD-9CM] 410.x; International Classification of Disease-10 Clinical Modification [ICD-10CM] I21.x-22.x) receiving ECMO support (ICD-9CM 39.65; ICD-10CM 5A15223) were identified consistent with prior literature [7]. Deyo's modification of Charlson Comorbidity Index was used to identify co-morbid diseases and prior methodology was used to identify cardiac and non-cardiac procedures [2,3,7,8,11,[13][14][15][16][17][18][19][20][21][22][23]. We identified relevant complications and categorized them as (a) vascular complications-arterial injury, acquired arterio-venous fistula, and vascular complications requiring surgery; (b) lower limb amputation; (c) hematologic-post-operative hemorrhage, hemolytic anemia, thrombocytopenia, and blood transfusion; and (d) neurologic-ischemic or hemorrhagic stroke ( Supplementary Table S1).…”
Section: Methodsmentioning
confidence: 99%
“…16 Demographic characteristics, hospital characteristics, acute organ failure, mechanical circulatory support, cardiac procedures, and noncardiac organ support use were identified for all admissions using previously used methods from our group. [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Similar to previous literature, we defined early coronary angiography (CA) as that performed on the day of hospital admission (day 0). 21,30,31 We identified the timing of CA and PCI relative to the day of admission.…”
Section: Study Population Variables and Outcomesmentioning
confidence: 99%